Impairment of Store-operated Calcium Entry: Implications in Alzheimer’s Neurodegeneration - Zhou, Jing; Wu, Shengzhou (Current Alzheimer Research, 2020)
Alzheimer's disease (AD) is an insidious and progressive neurodegenerative disorder. Dysfunction of central cholinergic neurons, amyloid aggregation and deposition,oxidative stress,and biometal dyshomeostasis has been regarded as the major pathogenic mediators in this devastating disease. However, strategies derived from these hypotheses fail to slow down or stop the progression of AD, warranting a combination of therapies to target multiple etiological factors or examining alternative hypothesis. Store-operated calcium entry (SOCE) is the process by which depletion of calcium in the endoplasmic reticulum (ER) lumen causes an influx of calcium across plasmalemma. Accumulating evidence indicates that neuronal SOCE (nSOCE) is inhibited in family AD (FAD) and the inhibition of which causes instability of dendritic spines and enhances amyloidogenesis. Mutant Presenilin fails to function as an ER calcium leak channel and promotes degradation of stromal interaction molecules (STIM), ER calcium sensors; these effects may account for the repression of nSOCE in FAD. We have demonstrated that activation of autophagy degrades STIM proteins, resulting in a trimming effect on a dendritic arbor, under proteasome inhibition and endoplasmic reticulum stress, which are intimately connected with AD. Thus, we hypothesize that autophagy represses SOCE by degrading STIM proteins, leading to synapse loss in AD. This review article will highlight the roles of SOCE in AD neurodegeneration, the degradative mechanisms of STIM protein, and the therapeutic potential and associated challenge.
Keywords: dendritic spine